y=(x+3)^2的原函数是( )
A: x+3
B: 1/3x^3+3x^2+9x+C
C: (x+3)^2
D: x^2+6x+9
A: x+3
B: 1/3x^3+3x^2+9x+C
C: (x+3)^2
D: x^2+6x+9
举一反三
- 设$f(x)=x^3$,则$f'(x+3)=3x^2$。
- 4x/(x²+x+3)+5x/(x²-5x+3)=-3/2
- (1)解不等式(3|x|-1)≤(|x|+3).(2)解不等式|x+3|-|2-x|>4.
- 方程y'(x) = x^2 - 3x + 2 的平衡点是 A: x = 1, x = 2 B: x = 3, x = 2 C: x = 3, x = 1 D: x = 3, x = 0
- 设函数$y = f({x^3})$可导,求函数的二阶导数$y'' = $( ) A: $6xf'({x^3}) + 9{x^4}f''({x^3})$ B: $6f'({x^3}) + 9{x^3}f''({x^3})$ C: $6xf'({x^3}) + 9{x^3}f''({x^3})$ D: $6{x^2}f'({x^3}) + 9{x^3}f''({x^3})$